simplify |x| - |-x|

Question

Asked 4/18/2011 11:38:30 AM

Updated 3/5/2014 2:18:18 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [3/5/2014 2:18:17 AM], Confirmed by andrewpallarca [3/5/2014 2:18:18 AM]

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Expert answered|topshi|Points 386|

Expert answered|topshi|Points 386|

Expert answered|topshi|Points 386|

Question

Asked 4/18/2011 11:38:30 AM

Updated 3/5/2014 2:18:18 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [3/5/2014 2:18:17 AM], Confirmed by andrewpallarca [3/5/2014 2:18:18 AM]

Rating

There are no new answers.

t Object]User: Simplify 10 + 4(x + 1) + 5 **Weegy:** 10 + 4(x + 1) + 5, 10 + 4x + 4 + 5= 4x + 19 **User:** Simplify 5(MN + 1) - 5 **Weegy:** 5(MN + 1) - 5 = 5MN **User:** Simplify 7(x + 2) + 12 **Weegy:** 7(x + 2) + 12 = 7x+26 **User:** Simplify 7(B + 3) + 2B (More)

Question

Expert Answered

Updated 3/5/2014 2:20:37 AM

1 Answer/Comment

7(B + 3) + 2B

7B + 21 + 2B

= 9B + 21

7B + 21 + 2B

= 9B + 21

Added 3/5/2014 2:20:37 AM

This answer has been confirmed as correct and helpful.

Simplify 2(x + y) + 3(x + y) **Weegy:** 2(x + y) + 3(x + y),
(2x + 2y) + (3x + 3y)
= 5x + 5y **User:** Simplify 8(C + 10) + 20 **Weegy:**
8(C + 10) + 20,
8C + 80 + 20,
= 8C + 100 **User:** Simplify 8(x + 6) - 10 **Weegy:**
8(x + 6) - 10,
8x + 48 - 10,
= 8x + 38 **User:** Simplify 6(x + 2) + 7 **Weegy:** 6(x + 2) + 7, 6x + 12 + 7 = 6x + 19 **User:** Which of the following expressions is equal to 5 - 2m?
A. 7 - 2(m + 1)
B. 7 - (2m - 5)
C. 7 - 2(m - 2) **Weegy:** 7-2(m+1) is equal to 5 - 2m **User:** Simplify 2x + x **Weegy:** 2x + x = 3x **User:** Simplify -3xy3 + 7xy3 + (-xy3) + (-3xy3) (More)

Question

Expert Answered

Updated 3/5/2014 2:25:08 AM

1 Answer/Comment

-3xy3 + 7xy3 + (-xy3) + (-3xy3)

= 0

= 0

Added 3/5/2014 2:25:08 AM

This answer has been confirmed as correct and helpful.

Simplify -3xy3 + 7xy3 + (-xy3) + (-3xy3)

Question

Expert Answered

Updated 5/25/2014 4:39:10 PM

2 Answers/Comments

-3xy^3 + 7xy^3 + (-xy^3) + (-3xy^3)

-3xy^3 + 7xy^3 -xy^3 -3xy^3

= 0

-3xy^3 + 7xy^3 -xy^3 -3xy^3

= 0

Added 5/25/2014 4:38:38 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/25/2014 4:45:13 PM]

(5b)(-3a) = -15ab

Added 5/25/2014 4:39:10 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/25/2014 4:45:23 PM]

Simplify -12x + 5x.
A.-7
B.-7x
C.-17x **Weegy:** -12x + 5x = -7x **User:** Simplify 5x + 4x + 1 **Weegy:** 5x + 4x + 1 = 9x + 1
**User:** Simplify 11(2x + 3) **Weegy:** 11(2x + 3) = 22x + 33 **User:** Simplify -2[9 - (x + 7)] (More)

Question

Expert Answered

Updated 3/5/2014 2:26:43 AM

1 Answer/Comment

-2[9 - (x + 7)]

-2[ 2 - x]

= 2x - 4

-2[ 2 - x]

= 2x - 4

Added 3/5/2014 2:26:43 AM

This answer has been confirmed as correct and helpful.

Simplify -2[9 - (x + 7)] **Weegy:** 5 (x -2) - 3( x - 4) = 10. In expanded form 2x+2=10. The answer x= 4. Click on the "Good" button. Thank you. (More)

Question

Updated 3/28/2015 8:44:58 AM

1 Answer/Comment

-2[9 - (x + 7)]

= -2[9 - x - 7]

= -2[2 - x]

= -4 + 2x

= -2[9 - x - 7]

= -2[2 - x]

= -4 + 2x

Added 3/28/2015 8:44:55 AM

This answer has been confirmed as correct and helpful.

37,282,811

questions answered

There are no comments.